(untitled) (Journal of Pharma Insights and Research, 2025)
Nigeria faces significant demographic changes with projections indicating that individuals aged 60 years and above will constitute over 10% of the population by 2050. The current healthcare infrastructure struggles to address the complex needs of the aging population while managing the dual burden of infectious diseases and chronic non-communicable conditions. Digital health technologies, artificial intelligence (AI), and telehealth platforms offer potential solutions to enhance healthcare delivery for older adults. A life-course approach to health demonstrates how early interventions and continuous care across different life stages influence health outcomes in later years. The use of AI-driven diagnostic tools, remote monitoring systems, and digital health platforms can facilitate early disease detection, improve care coordination, and increase healthcare accessibility, particularly in underserved regions. However, challenges such as infrastructure deficits, digital literacy gaps, and data privacy concerns need systematic attention. Strategic policy recommendations include developing comprehensive aging-inclusive digital health frameworks, strengthening healthcare worker training, establishing robust data protection mechanisms, and promoting public-private partnerships. The successful integration of digital health technologies requires consideration of cultural contexts, ethical implications, and social determinants while ensuring equitable access across urban and rural populations